PENCIPTAAN TOKOH SEDANG DALAM NASKAH TERDAMPAR KARYA TERJEMAHAN A. KASIM AHMA (JUDUL ASLI : NA PELNYM MORZU KARYA SLAWOMIR MROZEK) - bening, muhammad (Tonil: Jurnal Kajian Sastra, Teater dan Sinema, 2017)
The actor is one small part of a human who had more awareness of some part of reality. Thus the actor has a harder task in the sphere of reality they lived. Not just a matter of showing their existence by showing his talents on stage, but also the expertise to adapt to any form of reality he encountered to keep him exist in any reality. In the Terdampar script, maintaining the reality of human existence in space was happened. The ability of humans to change the reality, not as big as the ability of reality to change the humans. In Terdampar performance, the three characters which is Gendut, Sedang, and Kurus caught in the trap of the reality. They were then doing whatever can be done to maintain the existence of themselves. Keywords:Reality,human,Actor,Existence.